2011
DOI: 10.1128/aem.02588-10
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic-Phenotypic Discrepancies between Antibiotic Resistance Characteristics of Escherichia coli Isolates from Calves in Management Settings with High and Low Antibiotic Use

Abstract: We hypothesized that bacterial populations growing in the absence of antibiotics will accumulate more resistance gene mutations than bacterial populations growing in the presence of antibiotics. If this is so, the prevalence of dysfunctional resistance genes (resistance pseudogenes) could provide a measure of the level of antibiotic exposure present in a given environment. As a proof-of-concept test, we assayed field strains of Escherichia coli for their resistance genotypes using a resistance gene microarray … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
46
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 47 publications
6
46
0
Order By: Relevance
“…Here, more than 50% of these discrepancies were attributed to S. Dublin isolates from the Washington State clade, which carry an allele on a truncated strA that appeared to not confer STR resistance, while still being identified computationally as an STR resistance determinant. Similar discrepancies have been observed in a previous study (35) of Escherichia coli isolates from dairy calves; in this study, point mutations in strA were hypothesized to affect its ability to confer STR resistance. Additionally, a previous study that assessed phenotypic and genotypic resistance in nontyphoidal Salmonella isolated from retail meat and human clinical samples also found STR (P Ϫ :G ϩ ) discrepancies to be the most common (27).…”
Section: Discussionsupporting
confidence: 52%
“…Here, more than 50% of these discrepancies were attributed to S. Dublin isolates from the Washington State clade, which carry an allele on a truncated strA that appeared to not confer STR resistance, while still being identified computationally as an STR resistance determinant. Similar discrepancies have been observed in a previous study (35) of Escherichia coli isolates from dairy calves; in this study, point mutations in strA were hypothesized to affect its ability to confer STR resistance. Additionally, a previous study that assessed phenotypic and genotypic resistance in nontyphoidal Salmonella isolated from retail meat and human clinical samples also found STR (P Ϫ :G ϩ ) discrepancies to be the most common (27).…”
Section: Discussionsupporting
confidence: 52%
“…It is possible that these differences are related to some extend to the fact that adequate breakpoints are still to be defined for some compounds and that EUCAST epidemiological breakpoints for some compounds are very different from the CLSI clinical breakpoints. In E. coli, Davis et al [28] observed genotypic-phenotypic discrepancies to aminoglycosides in 24.7% of strains and characterised mutations or deletions in inactive AME genes in isolates where the gene was present but the expected corresponding phenotype resistance was absent.…”
Section: Discussionmentioning
confidence: 97%
“…Since then, CTX-M-type ESBLs have been found in E. coli collected from healthy dairy calves in the western U.S. (Davis et al, 2011) and from 5 of 20 dairy farms in Ohio (Mollenkopf et al, 2012); in clinical Salmonella enterica isolates from swine in Minnesota and from turkeys in 4 states (Wittum et al, 2012); in E. coli from swine finishing barns in Michigan and Ohio and in Klebsiella pneumoniae from swine in Illinois (Mollenkopf et al, 2013). …”
mentioning
confidence: 99%
“…Given the situation in other livestock species and in other countries, we expect the lack of detection of CTX-M-type ESBLs in U.S. chicken isolates is more the result of lack of appropriate studies than a real absence of these on chicken farms. In addition to CTX-M-type ESBLs, the study of dairy calves in the western U.S. also found E. coli expressing OXA-type ESBLs (Davis et al, 2011). …”
mentioning
confidence: 99%